PENGARUH KEMANDIRIAN KEUANGAN DAERAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA PROVINSI BANTEN - Stannia Cahaya Suci; Alla Asmara (IPB University, 2014)
Fiscal decentralization aims to improve regional finance independency and reduce the fiscal dependency of central government. However, in practice, there are many areas that still rely on the assistance central finance for their regional development. This research aims to discuss the development of regional finance independency and analyze the influence of regional finance independency on economic growth in Banten Province. This research uses descriptive method and panel data on 6 (six) regencies and cities in Banten Province at 2001-2011. The results showed the significantly positive effect of regional finance independency on economic growth and significantly negative effect of balance fund’s ratio on economic growth. Key words: local revenue, economic growth, panel data